Pengaruh Migrasi Terhadap Kemiskinan Rumah Tangga Perkotaan di Indonesia - Resaski, Atsilah; Marta, Joan (Universitas Negeri Padang, 2024)
The purpose of this study is to analyze the impact of migration on urban household poverty in Indonesia. This research uses a qualitative approach with secondary data from the 2020 National Socio-Economic Survey (SUSENAS). Based on the results, it is found that migration has a positive and significant effect on urban household poverty. And also control variables such as marital status and region of residence have a positive and significant effect. In contrast to the variables of gender, age, education and occupation which have a negative and significant effect.